2020
DOI: 10.2196/17238
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide Prevalence of Hearing Loss Among Smartphone Users: Cross-Sectional Study Using a Mobile-Based App

Abstract: Background In addition to the aging process, risk factors for hearing loss in adults include, among others, exposure to noise, use of ototoxic drugs, genetics, and limited access to medical care. Differences in exposure to these factors are bound to be reflected in the prevalence of hearing loss. Assessment of hearing loss can easily be carried out on a large scale and at low cost using mobile apps. Objective This study aimed to conduct a worldwide asse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Future studies with homogenous gold standards and uniform protocols for smartphone-based hearing tests are needed. Third, ambient noise monitoring is a key factor influencing the accuracy of audiometry [ 75 ]. Although most of the included studies did monitor noise, no data on the accuracy without ambient noise monitoring were provided.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies with homogenous gold standards and uniform protocols for smartphone-based hearing tests are needed. Third, ambient noise monitoring is a key factor influencing the accuracy of audiometry [ 75 ]. Although most of the included studies did monitor noise, no data on the accuracy without ambient noise monitoring were provided.…”
Section: Discussionmentioning
confidence: 99%
“…Sixth, of the 25 included studies, most did not describe the calibration method, whereas 9 (36%) used reference equivalent threshold sound pressure levels. A previous study revealed that the differences in hearing thresholds among the device models were significant, which might directly result from the biological calibration method used to determine the reference sound level [ 75 ]. Calibration information was lacking, possibly because of the intrinsic lack of a calibration function in the app.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, when the percentage of normal-hearing subjects in a study population is known, optimization can be performed on up to the same percentage of the best results, as they are bound to be within the norms. The percentage itself, can be easily estimated from, e.g., preliminary measurements or literature data [ 8 ] without having to check each subject for a normal hearing threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Communication difficulties, low self-esteem, and isolation lead to social exclusion and depression [ 1 , 2 , 3 ]. Currently, worldwide hearing loss prevalence is estimated between 4.0% and 18.1% [ 1 , 4 , 5 , 6 , 7 , 8 ]. Despite significant variation in the estimated values resulting primarily from the adopted methodology, the prevalence increases globally due to the aging of the worldwide population and the strong positive correlation between hearing impairment and age [ 4 , 5 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation